Physical fitness parameters of Chinese elite taekwondo athletes - Zhu, Y.; Li, Y.; Wenren, Y.; Gao, P. (International Journal of Morphology, 2025)
This study aimed to analyze the physical fitness parameters and their characteristics of Chinese elite taekwondo athletes and to propose corresponding training strategies. Twenty-seven Chinese national team taekwondo athletes were selected as the study subjects, including the 2024 Paris Olympic Games participants and the 2022 and 2023 World Taekwondo Championship medalists, totaling nine elite athletes. The test indexes included height, weight, BMI, the absolute strength of deep squat and bench press, 400 meters, 3000 meters, back up, V-up, hexagonal jump, standing long jump, and flexibility score. Compared to the ordinary athlete, Chinese male, and female elite taekwondo athletes did not show consistent characteristics in terms of height, weight, BMI, and other body morphology parameters, reflecting the fact that body morphology parameters are not a determining factor in the competitive performance of taekwondo athletes. Chinese female elite athletes with better performance in international competitions such as the Olympic Games showed better lower limb explosive power, back muscle strength endurance, aerobic and anaerobic endurance, agility, and hip flexibility.